Peran PMI di Lingkungan Kampus Universitas Islam Negeri Sumatera Utara (UINSU) - U, Usiono; Azahra, Bella; Harahap, Azmi Oktari; Sitompul, Buti Sarma (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Indonesian Red Cross (PMI) is a humanitarian organization that plays an important role in providing social assistance and community services, including in the campus environment of the State Islamic University of North Sumatra (UINSU). This study aims to explore the role of PMI, the types of programs implemented, and the obstacles faced in carrying out humanitarian activities at UINSU. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that PMI UINSU carried out various activities such as blood donation, first aid training, and health campaigns. However, student participation was still low due to lack of socialization and limited resources. Support from the campus is an important factor in increasing the effectiveness of PMI activities.